R&D spending patterns of global firms - Bowonder, B.; Racherla, J. K.; Mastakar, N. V.; Krishnan, S. (Research-Technology Management, 2005)
R&D spending by the top 320 companies in 2004 was US\$ 331 billion. The R&D intensity of these globalfirms has decreased marginally, as there was a decrease in R&D spending by pharmaceutical firms. R&D spending as a percentage of sales is the highest in the biotechnology industry followed by pharmaceuticals and network communications. At the same time, more firms are seeking to acquire intellectual assets from external sources. Managing intellectual assets will require competence to integrate external and internal knowledge assets so that innovation efficiency can go up while idea-to-market time goes down and product pipelines get richer.
Keywords: distributed innovation; globalization; R&D spending